Volatile monitoring of soil cuttings during drilling in cryogenic, water-doped lunar simulant. Issue 5 (1st September 2018) - Roush, Ted L.; Colaprete, Anthony; Cook, Amanda M.; Bielawski, Richard; Fritzler, Erin; Benton, Joshua; White, Bruce; Forgione, Joshua; Kleinhenz, Julie; Smith, James; Paulsen, Gale; Zacny, Kris; et al.
Abstract: NASA's Resource Prospector (RP) was intended to characterize the three dimensional volatile distribution near, and in, a permanently shadowed region on the moon. During May 2016 several RP hardware components were placed in a cryo-vacuum facility at NASA Glenn Research Center along with lunar simulant soil tubes prepared with varying amounts of water. The objective was simulation of observations during drilling activities on the lunar surface and assessing effective delivery of soil samples for capture and sealing. Here we report the spectral measurements ( ∼ 1600–3400 nm) obtained by one RP instrument while actively drilling. Spectral parameters related to two water ice spectral features near 2000 and 3000 nm were used to monitor the presence of water ice in real-time during drilling. Both parameters provide responses to the drilling activities as soil cuttings are emplaced on the surface and additionally document the sublimation of the ice from the cuttings. Qualitatively, the relative intensities of these parameters as a function of drill depth mimic post-test determinations of the soil water content. These results build confidence that the spectral data can provide information about volatile content in sub-surface materials as it is emplaced onto the surface on a time scale that can be used for real-time decision making regarding delivery of a sample to other analytical devices for more detailed characterization.